An Obesity Paradox of Asian Body Mass Index after Cardiac Surgery: Arterial Oxygenations in Duration of Mechanic Ventilation. (16th September 2013) - Chang, Chiu-Hsia; Lee, Fan-Yen; Wang, Chin-Chou; Chen, Ying-Ni; Chen, Hsin-Chu; Hung, Huei-Ling; Lin, Meng-Chih; Liu, Shih-Feng
Abstract : Background . Numerous studies have documented an obesity paradox that overweight of Caucasian patients has better prognosis after cardiac surgery. This study is to examine Asian patients' BMI to see whether an obesity paradox exists in DMV after cardiac surgery. Methods . A retrospective study consisted of 428 patients after cardiac surgery from January 2006 to December 2010 in the medical center of Taiwan. The Asian BMI was divided into 3 groups: under-normal weight patients (BMI < 24 ; n = 165 ), overweight patients (BMI 24 to <27; n = 130 ), and obese patients (BMI ≥ 27 ; n = 133 ). Multivariable analysis and paired t were used to compare all variables. Results . Overweight patients were significantly associated with the shortest DMV. Under-normal weight patients had significantly better oxygenations of AaDO2 and P/F ratio in the DMV; however, they correlated with the longest DMV, older age, more female, lower LVSV, higher BUN, more dialysis-dependent, and poorer outcomes, namely, 1-year mortality, HAP, reintubation, tracheotomy, and LOS. Conclusions . Asian overweight patients after cardiac surgery have better prognosis. Under-normal weight patients have higher risk factors, longer DMV, and poorer outcomes; even though they have better arterial oxygenations, they seem to need better arterial oxygenations for successful weaning ventilator.